Meningkatkan Pengetahuan tentang Kesetaraan Gender dan Inklusi Sosial bagi Masyarakat Desa Kampung Baru - Muhammad Zulhidayat; Dinda Fhara Afif Hafiza; Armelia Resti; Bq Mandalika; Rahma Meilinda; Rezi Andesta Putra; Muhammad Hasyim; Mismeidi Mismeidi; Talitha Ashila Deflides; Guspratama Yelli; Amalia Putri (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2023)
Gender equality is an interesting issue to discuss if you look at the pros and cons that are often attached to this issue. The issue of gender equality began to spread in Indonesia in the 1990s. Many people misinterpret gender equality as if it is seen as an act or desire to put women in the world first. However, this is not the goal of gender equality itself. This study uses a qualitative descriptive method, research data obtained by analyzing, describing, and summarizing various conditions, situations from various data collected in the form of interviews or observations regarding the problems studied that occur in the field. To help village development based on the SUSTAINABLE DEVELOPMENT GOALS (SDGs) it must include 8 goals so that the millennium development goals can be fulfilled in accordance with what has been set by the government, regardless of everyone's gender.